(untitled) (Al-Academy, 2015)
This takes research idea representations body in the works of artist Lisa Fattah al -Turk, and the qualities that represent them in the configuration and method of performance in order to achieve an important element in the development of the concepts of knowledge and cultural rights within the surface of the artwork including the body shape of his presence authority dominant in the history of art so it was for this audience motives Self , cultural , and part of the confirmation of the human side, and serves as a conveyor of ideas and diagnostic her.Search theme is determined to attend the address of the body in the works of artist Lisa Fattah al -Turk , a comparison in how the audience and what it will be , so Researcher seeks drilling in the artwork and self - dimensional detection , social and intellectual , which establishes a presence.1.Search begins with the problem down to determine the questions that seeks Find answered, including: What formal and aesthetic features to the presence of the body in the works of artist Lisa Fattah al –Turk?2.2. What qualities which represent the body in the works of artist Lisa Fattah al –Turk ?The results were: that the body come to work for reporting on social isolation in the ocean, and represents dropped to individual cases to see the outside world. The identity of the body and face theater which represents the changes the psychological, physical and temporal representation of it. That the body stores inside the Kingdom of the subconscious, which includes a magical world full of symbols, applies to reality as soon as it loses awareness of his authority. The conclusions came: the body vessel incubator of ideas and ideologies and concepts it stores inside accumulation of knowledge of mankind, and represents the social dimension, there is no body without the knowledge of tribal knowledge dimensionality. Said garment hides the body but they reveal the image of the body social, and environmental spatial and temporal through symbols. the two- body thought (Appearance substance ) ( self- body ) ( meaning building) this bilateral verification and the visible presence of the body in the world ( the perceived physical presence ) to form a harmonious unit , a humanitarian entity